The cAMP pathway and the control of adrenocortical development and growth - de Joussineau, Cyrille (2011)
In the last 10 years, extensive studies showed that the cAMP pathway is deregulated in patients suffering from adrenocortical tumours, and particularly in primary pigmented nodular adrenocortical disease (PPNAD). Here we describe how evidence arising from the analysis of patients’ data, mouse models and in vitro experiments, have shed light on the cAMP pathway as a central player in adrenal physiopathology. We also show how novel data generated from mouse models may point to new targets for potential therapies.